Policy Analysis and Implementation Impact of government subsidies on shared-bikes operation mode using system dynamics methodology: A case of Mobike in China. (September 2021) - Wang, Tengfei; Li, Hao; Xiao, Baorong; Wei, Di
This paper aims to explore the impact of government subsidy policies on strengthening the shared-bikes industry in China by simulating the operation mode of Mobike using system dynamics methodology. First, we introduce four subsidy policies: equalization subsidy, stage subsidy, growth subsidy, and back-slope subsidy, and establish a system dynamics model to characterize the bike-sharing operation dynamics system considering these four government subsidies. Subsequently, we analyze the impact of the four subsidy policies on enterprise-operating activities. The simulation results indicate that different subsidy policies have different incentive objectives and characteristics. The back-slope subsidy has more positive effects on enterprise operations in the short term but requires higher cost. The influence of growth subsidy and stage subsidy on enterprises can last longer, which requires the government to timely adjust the subsidy amount. The impact of equalization subsidy on enterprises is more stable, reducing government subsidy while ensuring enterprises' regular operation.